Pengaruh Lingkungan Kerja dan Motivasi Kerja Terhadap Kinerja Karyawan Pada PT. HM Sampoerna TBK Di DKI Jakarta - Mustika Baharsyah (Pusat Riset dan Inovasi Nasional, 2024)
The purpose of this research is to determine and analyze the influence of the work environment and work motivation on employee performance. The research method used was quantitative research method, where variables were measured using a Likert scale. Data collection methods include questionnaires, interviews and documentation. The research was conducted using a validity and reliability sample of 30 people taken from a total population of 385 people, while the research sample was 196 people using the Slovin method. Data processing uses SPSS version 26 software. The data analysis techniques use classical assumption tests, simple linear regression analysis, hypothesis testing, and coefficient of determination. The research results show that partially working environment variables has a significant and positive effect on employee performance. Partially, the work motivation variable has a significant and positive effect on employee performance.